Fenomena Belief Dilema dan Miskonsepsi Pengikut Buddha dalam Menjalankan Atthasila Saat Sebulan Pendalaman Dhamma - Bumi Horas (Educatio, 2025)
This research was motivated by the decreasing interest of Buddhists at the Sasanadipa Vihara to practice Atthasila during the Month of Dhamma Study leading up to Vesak. The purpose of this study was to analyze the existence of belief dilemma and misconception among followers of the Sasanadipa Makassar Buddhist Temple in carrying out Atthasila, the differences in factors that contribute to belief dilemma and misconception in three age groups of Buddhist followers, what factors can arouse the interest of a small number of followers of the Sasanadipa Makassar Buddhist Temple to practice Atthasila, and what factors trigger most Buddhist followers not to want to practice Atthasila. The implications of this study also explain the methods used to overcome the belief dilemma and misconception of followers of the Sasanadipa Makassar Buddhist Temple in carrying out Atthasila. Researchers use a qualitative descriptive approach, specifically analytical descriptive. The choice of this approach was to obtain a description of "The Phenomenon of Belief Dilemma and Misconceptions of Buddhists in Carrying out Atthasila During a Month of Dhamma Study". This research was conducted at the Sasanadipa Vihara, Makassar. The techniques used to collect data in this research consist of: 1. Observation, 2. Interviews, 3. Documentation. Researchers used three research instrument methods, namely observation, documentation and interviews. The results of this study indicate that: there are still belief dilemmas and misconceptions among followers of the Sasanadipa Buddha Vihara. The triggering factors are different in the 3 age groups of followers of the Sasanadipa Buddha Vihara studied. Each age group faces different challenges: adolescents are more concerned with physiological and social aspects, adults with work and health demands, and the elderly with health and family traditions.